2015
DOI: 10.1096/fj.15-272880
|View full text |Cite
|
Sign up to set email alerts
|

An intramolecular bond at cluster of differentiation 81 ectodomain is important for hepatitis C virus entry

Abstract: Hepatitis C virus (HCV) infection is one of the leading causes of chronic liver diseases; however, HCV vaccine remains unavailable to date. One main obstacle is the lack of an efficient small animal model. Cluster of differentiation 81 (CD81) is an essential entry coreceptor for HCV species specificity to humans, though the underlying mechanisms are yet to be fully elucidated. We performed structural, biophysical, and virologic studies on HCV nonpermissive CD81s from mice and African green monkeys [mouse clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…In both nanobody-bound structures, CD9EC2 adopts an arrangement that is globally similar to previously reported EC2-structures of CD81 (23,24,(40)(41)(42)(43). 4C8 and 4E8 bind nearly identical epitopes that span the C and D loops of CD9EC2 ( Fig.…”
Section: Crystal Structures Of Cd9ec2 In Complex With Nanobodiessupporting
confidence: 83%
See 2 more Smart Citations
“…In both nanobody-bound structures, CD9EC2 adopts an arrangement that is globally similar to previously reported EC2-structures of CD81 (23,24,(40)(41)(42)(43). 4C8 and 4E8 bind nearly identical epitopes that span the C and D loops of CD9EC2 ( Fig.…”
Section: Crystal Structures Of Cd9ec2 In Complex With Nanobodiessupporting
confidence: 83%
“…The EC2-D loop displays a high amino-acid sequence variability among tetraspanins and has been proposed to mediate homo-and hetero-oligomeric interactions (5,(44)(45)(46). Previously reported structures of CD81 revealed the conformational plasticity of its EC2 D-loop, with both fully helical and partially unfolded arrangements (23,24,(40)(41)(42)(43). Our nanobody-bound CD9EC2 structures also display a minor conformational difference in D-loop with respect to each other (Fig.…”
Section: Conformational Flexibility Of the Cd9ec2 D-loopsupporting
confidence: 52%
See 1 more Smart Citation
“…Disulfide bridges form loops comprising the g and g/d sections, respectively. Although a, b, and ε show little conformational variation, the structures differ in their VD (g and d), which is poorly resolved, suggesting conformational fluctuations even in the packed crystal lattices (20)(21)(22). In addition, a solution NMR study of the LEL showed pronounced conformational flexibility in this region (23).…”
Section: Introductionmentioning
confidence: 98%
“…To date, conformational variability has been observed only experimentally in the isolated LEL (20)(21)(22)(23), without membrane anchoring and other putatively stabilizing regions such as the SEL. This raises the question as to whether the observed flexibility is maintained in the membraneembedded, full-length protein.…”
Section: Introductionmentioning
confidence: 99%